Trends and challenges: Chinese students studying at south Korean universities / Andrea Rakushin Lee and Hak-Soo Yoo - Lee, Andrea Rakushin; Yoo, Hak-Soo (Universiti Teknologi MARA, 2022)
South Korea is a popular destination for Chinese students studying overseas. Prior to the pandemic, Chinese students comprised the largest percentage of foreign students in South Korea. This paper provides insights into major trends germane to Chinese students studying in South Korea. In addition, it explores challenges that Chinese students encounter while studying in South Korean universities, which include socialization problems, Korean and English language barriers, academic difficulties, and discrimination and prejudice. It also examines historical and political issues that have an impact on Chinese people living in South Korea. Strategies for improving successful integration are discussed. These include having effective academic and social support systems, promoting intercultural communicative competence, advanced preparation before leaving China, mutual adjustment activities that enhance understanding and awareness between different cultural groups, reflective practice and quality improvement, and exposure to diverse viewpoints. Finally, practical implications, which could improve the overall adaptation of Chinese students in South Korean universities are discussed.